IronRuby unleashed - Friedman, Shay (Unleashed., 2010)
Ruby has built an enormous following of developers attracted by its intuitiveness, flexibility, and simplicity. Meanwhile, Microsoft's .NET has grown and matured into a platform of unparalleled power. IronRuby brings them together, enabling developers to write elegant, efficient Ruby code that seamlessly integrates with .NET objects and leverages .NET's full capabilities. Now, in IronRuby Unleashed, one of IronRuby's most respected early adopters demonstrates how to write outstanding production software with the brand new IronRuby 1.0. Writing for both Ruby and .NET developers, Shay Friedman covers every facet of IronRuby programming. Friedman begins by explaining how IronRuby leverages the new Dynamic Language Runtime (DLR) libraries to run atop the .NET Framework and access its resources. Next, he presents an in-depth IronRuby tutorial that ranges from basic syntax and object-oriented programming techniques through advanced concepts. Building on this foundation, you'll learn how to make the most of a broad spectrum of .NET platform features. IronRuby Unleashed thoroughly illuminates the use of IronRuby and .NET with today's most powerful frameworks and technologies, including WPF, ASP.NET MVC, Ruby on Rails, and Silverlight. You'll also find detailed coverage of unit testing, as well as cutting-edge techniques for extending IronRuby with C# or VB.NET. Detailed information on how to ... Install IronRuby and choose the right development environment for your needs Master IronRuby syntax, methods, blocks, classes, modules, libraries, and more Write code that takes advantage of IronRuby's dynamic and metaprogramming features Utilize .NET services and frameworks to write more powerful Ruby code than ever before Incorporate efficient data access into your IronRuby applications Use IronRuby to build Windows software with both WinForms and WPF Rapidly build high-quality Web applications with IronRuby and Ruby on Rails Create rich Web 2.0 applications with IronRuby and Microsoft Silverlight Test .NET code with Ruby's leading unit testing frameworks Run IronRuby code from other .NET code, and create .NET code libraries that fit well with IronRuby code.